Civic Engagement in Contemporary Japan Established and Emerging Repertoires - Vinken, Henk.; Nishimura, Yuko.; White, Bruce L. J.; Deguchi, Masayuki; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
With a variety of contributors from throughout Japan, involved in a range of both established and emerging forms of civic engagement from NGOs, NPOs, to other less mainstream organizations, the Editors have compiled a comprehensive volume to give a thorough insiders$1 (Blook at the state of civil society in Japan. Established forms of civic engagement include labor unions, and resident and citizens$1 (Bmovements dating back centuries. In more recent years, Japan has seen a rise in third sector groups that parallels a rise worldwide, especially grassroots community organizations. From political engagement, to underground media, the authors of this volume closely examine Japans$1 (Bdevelopment in civic engagement. The lessons gleaned from the successes and shortcomings of civic engagement in Japan have strong applications internationally. The detailed and comprehensive coverage of this volume make it a useful resource for understanding not only Japanese social and political issues, but also the emergence of third sector organizations worldwide$1 (Bwhat works, what does not work as well, and what organizational structures are possible.s
Introductory section -- Civil Society in Japan: Democracy, Voluntary Action, and Philanthropy -- Social Frameworks for Civil Society in Japan: In Search for a Japanese Model -- Established forms of engagement -- The Rising Voice of Japan$1 (Bs Community Unions -- Collaborative Environmentalism in Japan -- A New Epoch of Immigration for Japan: Directional Shift in Civic Organizational Support for Newcomer Settlement -- Engagement outside the mainstream -- Civic Engagement and Community Development Among Japan$1 (Bs Burakumin -- (3z(BI$1 (Bm Deaf. This is Sign. Get Used to It.(3y (BSign Language in Japan: The Vision and the Struggle -- Media and Civic Engagement in Japan -- Emerging forms of engagement -- The Soft Advocacy of Music Fandom: Japanese Youth and the Building of Civic Infrastructures of the Mind -- Re-imagining the Relationship Between Japan and Korea: Popular Culture and Civic Engagement -- Fun with Consumers: Enjoying Anticonsumerism in Japan -- Concluding section -- Conclusions: From Politicization to Culturalization of Civic Engagement -- Epilogue: Toward a New Legal Form for Civic Engagement.s
Keywords: Social sciences; Regional planning; International economics; Social policy; Social Sciences; Sociology, general; Social Policy; Regional and Cultural Studies; International Economics